An exploratory study of the relationship between systemic microcirculatory function and small solute transport in incident peritoneal dialysis patients. Issue 5 (September 2022) - Williams, Jennifer; Gilchrist, Mark; Strain, William David; Fraser, Donald; Shore, Angela
Background: The peritoneal capillary endothelium is widely considered to be the most influential structure in dictating the rate of small solute transport (SST) during peritoneal dialysis (PD). PD patients are at significant risk of systemic microcirculatory dysfunction. The relationship between peritoneal and systemic microcirculations in patients new to PD has not been well studied. We hypothesised that for patients on PD for less than 6 months, dysfunction in the systemic microcirculation would be reflected in the rate of SST. Methods: We recruited 29 patients to a cross-sectional, observational study. Rate of SST was measured using a standard peritoneal equilibration test. Laser Doppler Flowmetry was used to measure response to physical and pharmacological challenge (post-occlusive hyperaemic response and iontophoretic application of vasodilators) in the cutaneous microcirculation. Sidestream Darkfield imaging was used to assess sublingual microvascular density, flow and endothelial barrier properties. Results: We found no moderate or strong correlations between any of the measures of systemic microcirculatory function and rate of SST or albumin clearance. There was however a significant correlation between dialysate interleukin-6 concentrations and both SST ( rs = 0.758 p ≤ 0.0001) and albumin clearance ( rs = 0.53, p = 0.01). Conclusions: In this study, systemic microvascular dysfunction did not significantly influence the rate of SST even early in patients PD careers. In conclusion, this study demonstrates that intraperitoneal factors particularly inflammation have a far greater impact on rate of SST than systemic factors.